Results from the 2001-2002 National Farm Crime Survey - McCall, Marissa; Australian Institute of Criminology (Canberra : Australian Institute of Criminology, 2003)
This paper summarises results from the second National Farm Crime Survey. It examines the type, extent and cost of property crime being committed on Australian broadacre and dairy farms. Overall, results show that crime has decreased slightly but is costing farmers more financially. Repeat victimisation is quite high. Only half of all crime experienced on farms was reported to the police. The experience of crime varied by farm accessibility and farm size. Further research should focus on what needs to be done to prevent crime from occurring on farms.
Caption title.
"October 2003".
Invalid ISBN appears on publication: 0642538203.
Includes bibliographical references (p. 6).
Also available in an electronic version via the Internet at: http://www.aic.gov.au/publications/tandi2/tandi266.pdf
Keywords: Victims of crimes surveys -- Australia; Rural crimes -- Australia -- Statistics; Farmers -- Crimes against -- Australia -- Statistics